Effects of temperature, food type and food concentration on the grazing of the calanoid copepod Centropages chierchiae - Garrido, Susana (2013)
Laboratory experiments were conducted to study the combined effect of temperature (8, 13, 19 and 24C), food type and food concentration on the grazing rates of the adult stages of the calanoid copepod Centropages chierchiae. As prey, the diatom Phaeodactylum tricornutum and the dinoflagellate Gymnodinium sp. (both ca. 15 m cell diameter) were used at a range of carbon concentrations similar to the ones experienced in nature (6.4 to 393.8 C L-1). Ingestion rates increased linearly with food concentration and did not differ between prey types. When comparing the effect of temperature, highest clearance and ingestion rates were obtained at 19C, whereas no difference was observed among the other temperatures. Daily rations varied between 1.2 and 183.5 body carbon day(1). Additional experiments were conducted to study the selective feeding behaviour of C. chierchiae when offered a mixture of different prey types. Selective feeding was dependent on food concentration; at low food levels, large cells were selected (Ditylum brightwellii), whereas at medium and high food concentrations no clear selection patterns were observed. In contrast to other studies, no positive selection of dinoflagellates over other algal food was found.